2019
DOI: 10.3390/su11051441
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Ownership Structure on the Determinants of Effective Tax Rates of Spanish Companies

Abstract: This paper examines the effect of state ownership on the effective tax rates of Spanish companies. Using information regarding 3169 companies during the period of 2008–2014, we show that there are significant differences between the tax burdens of non-state-owned enterprises (NSOEs) and state-owned enterprises (SOEs), with the effective tax rates of private ownership companies being higher than those of state-owned firms. Company features, such as size, leverage, research and development investment, profitabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
1
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 47 publications
1
22
1
4
Order By: Relevance
“…Jindrichovska et al [18], on the case of 260 Czech firms, also found a negative relationship between growth of tangible assets, as a share of total assets, and return on assets Sustainability 2020, 12, 1689 4 of 18 of those firms. Fernández-Rodríguez et al [19], while examining the influence of ownership structure on tax rates of Spanish firms, found that growth of fixed assets, expressed by capital intensity, has a negative and significant relationship with effective tax rate of the state owned companies, expressed as a relationship between tax expense and pretax income. Aljinović Barać and Muminović [20], on the case of dairy processing industry in Slovenia, Croatia, and Serbia found that companies with higher level of capital investments per employee obtain lower financial performance, expressed by return on assets, and that possible explanation for that can be found in the time lag between the moment of investment and the moment in the future when investment will generate the profit.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Jindrichovska et al [18], on the case of 260 Czech firms, also found a negative relationship between growth of tangible assets, as a share of total assets, and return on assets Sustainability 2020, 12, 1689 4 of 18 of those firms. Fernández-Rodríguez et al [19], while examining the influence of ownership structure on tax rates of Spanish firms, found that growth of fixed assets, expressed by capital intensity, has a negative and significant relationship with effective tax rate of the state owned companies, expressed as a relationship between tax expense and pretax income. Aljinović Barać and Muminović [20], on the case of dairy processing industry in Slovenia, Croatia, and Serbia found that companies with higher level of capital investments per employee obtain lower financial performance, expressed by return on assets, and that possible explanation for that can be found in the time lag between the moment of investment and the moment in the future when investment will generate the profit.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A study by Congressional Budget Office (GAO, 2008) revealed that Effective tax rates are always lower than the statutory tax rates. Similarly a study by Pomerleau and Jahnsen (2017) and Fernandez-Rodriguez, Garcia-Fernandez and Martinez-Arias (2019) also shows that ETRs are always lower than the statutory tax rates.…”
Section: Introductionmentioning
confidence: 67%
“…Firms that reported losses in the period are excluded from the sample since negative ETR has no meaning. This follows the usual procedure from previous studies (Fernandez-Rodriguez et al, 2019). Secondary data was extracted from published financial statements for the period 2011 to 2017 using a content analysis form.…”
Section: Methodsmentioning
confidence: 99%
“…Low financial efficiency and low or high financial competition will reduce the R & D efficiency of the company [14]. Elena fern á nude Rodr íGuez (2019) pointed out in the study of Spanish sustainable enterprises that the tax preference provided by law to support its sustainability may make the effective tax rate of state-owned enterprises lower than that of non-state-owned enterprises [15].…”
Section: Sustainable Development Trendmentioning
confidence: 99%